AN ECONOMIC-AND-MATHEMATICAL MODEL OF OPENING PARAMETERS OF PREPARATION WORKS - A. H. Vahonova; T. A. Jerokhondyna; O. O. Shashenko (Nauka ta progres transportu, 2010)
We propose an economic-and-mathematical model of opening and preparation of mine field based on the graph theory. The model is optimized by the factor of minimum amounts of conducting the preparation underground works.